Geoarchaeological and Paleoenvironmental context of the human settlement in the Eastern Tandilia Range, Argentina - Martinez, Gustavo Adolfo (2013)
The Tandilia range is a discontinuous series of hills and valleys located at the central area of the Pampean region (Argentina). The process of human settlement reached in this zone the highest population densities and reoccupation levels of Southern South America, developing under the strongly changing climatic conditions that characterized the Pleistocene–Holocene transition. This paper analyzes the geoarchaeological and paleoenvironmental record of the Pleistocene–Holocene transition (c. 9400–10,500 14C BP) recovered from cave and rockshelter sedimentary successions of the Tandilia range. The analysis of several lines of evidence (stratigraphic, geoarchaeological, archaeological, zooarchaeological, and paleobotanical), suggests that a cold arid to semi-arid climate characterized the late Pleistocene (c. 10,500 BP), and changed abruptly to warmer conditions towards the beginning of the Post-Glacial Period. As a consequence of this climatic amelioration, the populations inhabiting the Tandilia range would have been benefited by a higher availability of resources, which could explain the higher levels of site density and reoccupation found in the area during this period.